The relationship between tolerance for uncertainty and creativity among high school students with a critical style of thinking - Alla K. Belousova; Alena V. Samarskaya; Ekaterina V. Kryazhkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents the results of a study of tolerance relation to uncertainty and creativity among senior schoolchildren with a critical style of thinking. The authors use valid diagnostic methods: A. Belousovas thinking style questionnaire, S. Badners uncertainty tolerance questionnaire, and P. Torrances test. The sample consists of 90 senior schoolchildren, both boys and girls. As a result of the study, the groups of schoolchildren with a dominant critical and practical style of thinking have been identified. The authors show that there are significant differences in the development of relationships between uncertainty and creativity tolerance scales, between uncertainty tolerance and critical thinking style, creativity and critical thinking style. The differences have been obtained in the development of tolerance for uncertainty, creativity in relation to the practical style of thinking.